2020
DOI: 10.1101/2020.12.23.424168
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Neoantigen driven B cell and CD4+T follicular helper cell collaboration promotes robust anti-tumor CD8+T cell responses

Abstract: CD4+ T follicular helper (TFH) cells provide help to B cells, which is critical for germinal center (GC) formation, but the importance of TFH-B cell interactions in cancer is unclear. We found TFH cells correlated with GC B cells and with prolonged survival of lung adenocarcinoma (LUAD) patients. To investigate further, we developed an LUAD model, in which tumor cells expressed B-cell- and T-cell-recognized neoantigens. Interactions between tumor-specific TFH and GC B cells were necessary for tumor control, as… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 142 publications
(38 reference statements)
0
10
0
Order By: Relevance
“…Germinal center (GC) B cells could be activated by TFH-B interaction and further differentiate into short-term living plasma cells, long-term living plasmablasts, and memory B cells. The singlecell RNA sequencing result of tumor-infiltrating lymphocytes in many studies revealed the presence of GC B cells in the TME (9,16), yet the role of GC B cells is not well known. The study done by Cui et al in lung adenocarcinoma patients elucidated that GC B cells facilitate the function of CD8 + T cells in antitumor immunity via the TFH-GC B cell interaction in a neoantigen-dependent manner (9).…”
Section: Antigen-presenting Cellsmentioning
confidence: 99%
See 3 more Smart Citations
“…Germinal center (GC) B cells could be activated by TFH-B interaction and further differentiate into short-term living plasma cells, long-term living plasmablasts, and memory B cells. The singlecell RNA sequencing result of tumor-infiltrating lymphocytes in many studies revealed the presence of GC B cells in the TME (9,16), yet the role of GC B cells is not well known. The study done by Cui et al in lung adenocarcinoma patients elucidated that GC B cells facilitate the function of CD8 + T cells in antitumor immunity via the TFH-GC B cell interaction in a neoantigen-dependent manner (9).…”
Section: Antigen-presenting Cellsmentioning
confidence: 99%
“…The singlecell RNA sequencing result of tumor-infiltrating lymphocytes in many studies revealed the presence of GC B cells in the TME (9,16), yet the role of GC B cells is not well known. The study done by Cui et al in lung adenocarcinoma patients elucidated that GC B cells facilitate the function of CD8 + T cells in antitumor immunity via the TFH-GC B cell interaction in a neoantigen-dependent manner (9). They utilized a lung adenocarcinoma cell line (KP) with limited somatic mutations, which means that there are few or no neoantigen expression and weak B/T cell responses so that B cell or T cell depletion doesn't affect the tumor growth.…”
Section: Antigen-presenting Cellsmentioning
confidence: 99%
See 2 more Smart Citations
“…B cell frequency in tumor is positively correlated with patient survival, representing a novel prognostic cellular biomarker (21). Moreover, the presence of B cells in tertiary lymphoid structure (TLS) is positively associated with protective tumor immunity, including high levels of naïve, memory, and activated T cells, and low levels of exhausted T cells and Tregs (22)(23)(24).…”
Section: Introductionmentioning
confidence: 99%